Examining the Effects of Intellectual Capital on Dynamic Capabilities in Emerging Economy Context: Knowledge Management Processes as a Mediator. (May 2016) - Singh, Bindu; Rao, M.K.
Abstract: This study aims to examine the effects of intellectual capital on dynamic capabilities and the mediating role of knowledge management processes. Based on the review of literature, a research model was proposed to examine this quantitative relationship. The model was empirically tested using 679 responses from the banking industry in India and applying Structural equation modeling analysis. It was found that intellectual capital with its three dimensions has significant effect on dynamic capabilities. Concerning to mediating role of knowledge management process, two patterns of association was found: Knowledge management process partially mediates the effect of organizational capital on dynamic capabilities and fully mediates the effect of human capital and social capital on dynamic capabilities. Based on these empirical insights, inferences and future avenues are further discussed in detail.